Testing a new type of fertilizer to improve nursery production of framework tree species for forest ecosystem restoration in Northern Thailand - Panya Waiboonya (2020)
© 2019, Chiang Mai University. To improve planting-stock production of native forest tree species for tropical forest ecosystem restoration projects in northern Thailand, we compared a new controlled-release fertilizer, developed by NANOTEC, with our current standard fertilizer treatment for its effects on sapling growth and biomass allocation in a small-scale tree nursery. Eight species were tested: Artocarpus lacucha, Adenanthera microsperma, Acrocarpus fraxinifolius, Hovenia dulcis, Horsfieldia amygdalina, Phyllanthus emblica, Prunus cerasoides and Syzygium albiflorum, using a randomized complete block design with three treatments x three replicates of nine plants per replicate for each of the eight species. The treatments were NANOTEC fertilizer, applied once at doses 0.30 g or 0.15 g per sapling, two weeks after pricking out small seedlings from germination trays into plastic bags 23 cm × 6 cm, compared with 0.30 g Osmocote® 13:13:13 (our current most effective fertilizer treatment). Sapling growth (height, crown width and root collar diameter) was then measured over 121 days. The new NANOTEC fertilizer, at both doses, performed equally as well as Osmocote®. With very few exceptions, differences in mean sapling growth performance, biomass, root:shoot ratioand remaining nutrients (N, P and K) in the potting medium, among all the fertilizer treatments, were not statistically significant, for every individual species and when treatment data were combined for all species. Consequently, the locally produced NANOTEC fertilizer, at 0.15 g/tree, could be used as a cost-effective substitute for 0.30 g Osmocote®, provided that its retail price is similar to or lower than that of Osmocote®, when it enters mass production.